1984
DOI: 10.1071/ea9840260
|View full text |Cite
|
Sign up to set email alerts
|

Migration of stored-grain insect pests from a small wheat bulk

Abstract: One hundred unsexed adults of each of the following coleopterous species were added to 27 .3 kg of clean wheat: Sitophilus oryzae (L.) (rice weevil), Rhyzopertha dominica (F.) (lesser grain borer), Tribolium castaneum (Herbst) (rust-red flour beetle), and the flat grain beetles Cryptolestes pusillus (Schonherr), C. ferrugineus (Stephens), and C. pusilloides (Steele and Howe). For 15 months, measurements were made of population size and emigration from this wheat bulk. The highest populations recorded for each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
2
5
0
Order By: Relevance
“…In Australia, Wright & Morton (1995) found that 16 °C was the minimum temperature threshold for flight, but Sinclair & Alder (1984) estimated a threshold of 21.5 °C. In Australia, Wright & Morton (1995) found that 16 °C was the minimum temperature threshold for flight, but Sinclair & Alder (1984) estimated a threshold of 21.5 °C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Australia, Wright & Morton (1995) found that 16 °C was the minimum temperature threshold for flight, but Sinclair & Alder (1984) estimated a threshold of 21.5 °C. In Australia, Wright & Morton (1995) found that 16 °C was the minimum temperature threshold for flight, but Sinclair & Alder (1984) estimated a threshold of 21.5 °C.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the lower temperature threshold for R. dominica flight activity in the autumn vs. summer conditions may, in part, explain variable reports in the literature. In Australia, Wright & Morton (1995) found that 16 °C was the minimum temperature threshold for flight, but Sinclair & Alder (1984) estimated a threshold of 21.5 °C. Dowdy (1994) reported a lower flight threshold of 19.9 °C in the USA.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these would influence the contribution of individual immigrants to gene flow. Tribolium castaneum beetles have been recorded emigrating from bags of flour in the laboratory (Hagstrum & Gilbert 1976) and from a small (<25 kg) artificially infested bulk of wheat (Sinclair & Alder 1984), but the situation in the field remains unclear. If females emigrate from grain storages in the field, they need to be characterized in terms of their survival rate, mating status and reproductive potential to understand how the movement of individual beetles relates to measures of gene flow obtained from the field.…”
Section: Introductionmentioning
confidence: 99%
“…Mistargeting will result in untreated spots with pests, and infestation resurgence can be expected. Another potential problem associated with this method is that the emigrated (Sinclair & Alder 1984) and undetected pests in the vicinity of fumigated spots are treated inefficiently, and such exposure to low or sublethal gas doses poses a risk (Phillips et al 2001) that the most sensitive individuals from the population are eliminated, which will lead to an increase in PH 3 resistance.…”
Section: Resultsmentioning
confidence: 99%
“…We focused on the efficacy of PH 3 not only within the fumigated spot, but also in the surrounding areas because pests tend to migrate intensively in the grain. Sinclair and Alder (1984) documented that pests migrate in and outside stored grain mass even when populations are low.…”
mentioning
confidence: 99%